2000
DOI: 10.1002/j.1556-6676.2000.tb02576.x
|View full text |Cite
|
Sign up to set email alerts
|

Student Perceptions of Campus Cultural Climate by Race

Abstract: Five hundred and seventy-eight African American, Asian American, Latino/a, and White undergraduates responded to a questionnaire assessing perceptions and experiences of the campus cultural climate. Results revealed significant differences between racial and ethnic groups on multiple dimensions of the campus cultural climate. African American students consistently reported significantly more racial-ethnic conflict on campus; pressure to conform to stereotypes; and less equitable treatment by faculty, staff, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
273
3
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 364 publications
(303 citation statements)
references
References 25 publications
26
273
3
1
Order By: Relevance
“…First, we examined the relationship between individual factors and cognitive process variables using undergraduate students as little attention has been devoted to their experiences of cognitive processes (Goto & Takeuchi 2002;Greenland & Brown 1999), particularly in an Australian context. We substantiated the findings of previous studies mostly conducted in the United States that gender is a predictor of anxiety & apprehension (Tsui, Egan & O'Reilly 1992) and nationality is a predictor of bias (Ancis, Sedlacek & Mohr 2000;Kessler, Michelson & Williams 1999;Kohatsu et al 2000;Pham & Dykstra 1994), stereotyping (Pham & Dykstra 1994) and anxiety & apprehension (Lau et al 2009;Okazaki 1997;Okazaki et al 2002). However, we found that the relationships between gender and bias, and gender and stereotyping were not statistically significant.…”
Section: Discussionsupporting
confidence: 90%
“…First, we examined the relationship between individual factors and cognitive process variables using undergraduate students as little attention has been devoted to their experiences of cognitive processes (Goto & Takeuchi 2002;Greenland & Brown 1999), particularly in an Australian context. We substantiated the findings of previous studies mostly conducted in the United States that gender is a predictor of anxiety & apprehension (Tsui, Egan & O'Reilly 1992) and nationality is a predictor of bias (Ancis, Sedlacek & Mohr 2000;Kessler, Michelson & Williams 1999;Kohatsu et al 2000;Pham & Dykstra 1994), stereotyping (Pham & Dykstra 1994) and anxiety & apprehension (Lau et al 2009;Okazaki 1997;Okazaki et al 2002). However, we found that the relationships between gender and bias, and gender and stereotyping were not statistically significant.…”
Section: Discussionsupporting
confidence: 90%
“…The following three blocks-institutional characteristics, student major field, and major field climate-reflect college environments. Based on the findings from research that students' field of study (Astin 1993;Astin and Holland 1961;Smart et al 2000) and perceptions of campus cultural environments (Ancis et al 2000;Colbeck et al 2001;Hurtado 1992;Hurtado et al 1996) may significantly affect their college experiences and outcomes, this study employed students' major fields and major field climate as part of college environment variables along with institutional characteristics. The last block of control variables includes college experiences and captures a student's direct experience and involvement during college.…”
mentioning
confidence: 99%
“…Researchers argue that the biased practices of many PWIs contribute to minority students' cultural shock and alienation (Ancis, Sedlacek, & Mohr, 2000;Just, 1999;Lui & Lui, 2000Just (1999 argues that racial climate influences almost every aspect of minority students' college experience, leading to academic and social marginalization.…”
Section: Department Of Educationmentioning
confidence: 99%